2013
DOI: 10.1093/humrep/det249
|View full text |Cite
|
Sign up to set email alerts
|

GnRHa trigger and individualized luteal phase hCG support according to ovarian response to stimulation: two prospective randomized controlled multi-centre studies in IVF patients

Abstract: Although a non-significant result, one bolus of 1.500 IU hCG after GnRHa trigger tended to reduce the OHSS rate in patients with 15-25 follicles ≥11 mm as well as secure the ongoing pregnancy rate. In contrast, in patients at low risk of OHSS the administration of two boluses of 1.500 IU hCG after GnRHa trigger should be avoided as it may induce OHSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
184
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(191 citation statements)
references
References 41 publications
3
184
0
3
Order By: Relevance
“…Bunun yanında over stimulasyonunun etkisiyle yüksek estradiol seviyelerine bağlı ilişki sonrası daha uzun süre spermlerin servikal mukusda canlı kalabileceği literatürde bildirilmiştir (16) GnRH agonistlerinin tetiklediği LH artışı muhtemelen korpus luteum fonksiyonlarının devamını sağlamak için yeterli olmamaktadır. Bu nedenle düşük doz hCG, ya GnRH agonistleri ile beraber ya da oosit toplama işlemi öncesi uygulanabilir (15,17). Primatlarda pituiter gonadotropin desteği olmadan eksojen uygulanan LH desteğinin 3 gün içerisinde sağlanması ile corpus luteumun devam edebildiği görülmüştür (18).…”
Section: Discussionunclassified
“…Bunun yanında over stimulasyonunun etkisiyle yüksek estradiol seviyelerine bağlı ilişki sonrası daha uzun süre spermlerin servikal mukusda canlı kalabileceği literatürde bildirilmiştir (16) GnRH agonistlerinin tetiklediği LH artışı muhtemelen korpus luteum fonksiyonlarının devamını sağlamak için yeterli olmamaktadır. Bu nedenle düşük doz hCG, ya GnRH agonistleri ile beraber ya da oosit toplama işlemi öncesi uygulanabilir (15,17). Primatlarda pituiter gonadotropin desteği olmadan eksojen uygulanan LH desteğinin 3 gün içerisinde sağlanması ile corpus luteumun devam edebildiği görülmüştür (18).…”
Section: Discussionunclassified
“…The now wellestablished bolus dose of 1500 IU of hCG to stimulate CL function given at the time of OPU will result in hCG concentrations of around 30-50 IU/l tailing off to reach low concentrations around the mid-luteal phase. Administrating two bolus injections of 1500 IU (day OPU and day OPU + 5) in normally responding women [9] resulted in hCG levels around 40-60 IU/l during the mid-luteal phase, hence resulting in a slightly increased risk of OHSS (Fig. 4).…”
Section: Micro-dose Hcg Stimulation As Luteal Phase Support Mathematimentioning
confidence: 99%
“…In recent years, the GnRH agonist (GnRHa) trigger has been used as an alternative to the hCG trigger in patients following the antagonist protocol [7][8][9]. The GnRHa trigger Capsule It is suggested that the currently employed LPS provided in connection with the GnRHa trigger (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations